A concepção de homem no Behaviorismo radical e suas implicações para a tecnologia do comportamento - Melo, Camila Muchon de (2008)
B. F. Skinner describes and explains the human behavior through the causal model of selection by consequences. According to this model, the human behavior is the product of the interaction among three levels of variability and selection (phylogeny, ontogeny and culture). According to this explanation, the cultural contingencies enable the rising and maintenance of behaviors that may produce consequences which strengthen a culture and these are the behaviors which participate as operant behaviors in the constituting of a cultural practice. The Man is a product of three processes of variation and selection. Within this, especially due to the third level, he is a Man that may also plan new variations which may perform a role on the strengthening of a culture and therefore he must plan contingencies so that the behavior produces the good of the culture. The cultural planning directed to the survival of the culture elicits questionings on the Behavioral Technology proposed to enable the insertion of new cultural practices. Thus, this study had the objective of investigating if the conception of Man in Radical Behaviorism in Skinner s works, interpreted as a commitment with the good of the culture, is consistent with the proposal of this author of a Behavioral Technology. Aspects of Science and Ethics based on the Philosophy of Radical Behaviorism have been investigated. Moreover, some examples of behavioral technology based on this philosophy have illustrated our analyses in the defense of a technology which produce consequences which may strengthen a culture. Using methods of text analyses and of epistemological-hermeneutic, texts from the author previously selected which refer to the concepts of Man, culture, science, ethics and technology have been analyzed in order to identify the inconsistencies, clarify or explain the conception of Man and Behavioral Technology proposed by the model of selection by consequences of the Skinner s Radical Behaviorism.